(untitled) (Fiep Bulletin - online, 2025)
Introduction: Public parks have emerged as spaces that contribute to promoting health and well-being among visitors, positively influencing their self-perceived health. Objective: To assess the prevalence and factors associated with self-perceived health among visitors to public parks in Teresina, PI. Methods: This is a descriptive, cross-sectional study conducted with a sample of 102 adult visitors from two public parks in Teresina, Piauí. The online questionnaire for data collection included a question about self-perceived health: "How do you rate your health?" along with sociodemographic, behavioral, and health characteristics. Statistical analysis included descriptive measures of absolute and relative frequency and Pearson’s chi-square test, with p-values <0.05 considered significant. Results: The prevalence of positive self-perceived health was 72.5% among park visitors. Most (53.9%) had no comorbidities, were physically active (64.7%), did not smoke (83.3%), and reported not using continuous medications (52.9%). Negative self-perceived health was higher among visitors with a greater number of comorbidities (p-value 0.018), those using continuous medications (p-value 0.011), and smokers (p-value 0.010). Conclusion: Factors related to health conditions were associated with visitors’ individual health perception. Public parks can contribute to promoting a healthy lifestyle and overall well-being of the population.